Delayed tooth eruption in Down syndrome: critical appraisal of evidence - Rivas-Almonte, Ursula Ofelia (2021)
Down syndrome in children is associated with multiple orofacial alterations, among them delayed tooth eruption has been mentioned, the understanding of which is not yet fully known. A review was carried out to analyze the concepts of tooth eruption and the available evidence regarding delayed tooth eruption in children with Down syndrome, and its relationship with tooth maturation or with other systemic and local factors. Few studies were observed on the subject, however, with the found literature it was possible to conclude that the delay in tooth eruption seems not to be related to the maturation of the tooth, but it is related to other processes that take place during tooth eruption or it may be part of the general delay in growth and development that characterizes Down syndrome.